Regulation of anti-microbial autophagy by factors of the complement system - Christophe Viret; Aurore Rozières; Rémi Duclaux-Loras; Gilles Boschetti; Stéphane Nancey; Mathias Faure (Microbial Cell)
The complement system is a major component of innate immunity that participates in the defense of the host against a myriad of pathogenic microorganisms. Activation of complement allows for both local inflammatory response and physical elimination of microbes through phagocytosis or lysis. The system is highly efficient and is therefore finely regulated. In addition to these well-established properties, recent works have revealed that components of the complement system can be involved in a variety of other functions including in autophagy, the conserved mechanism that allows for the targeting and degradation of cytosolic materials by the lysosomal pathway after confining them into specialized organelles called autophagosomes. Besides impacting cell death, development or metabolism, the complement factors-autophagy connection can greatly modulate the cell autonomous, anti-microbial activity of autophagy: xenophagy. Both surface receptor-ligand interactions and intracellular interactions are involved in the modulation of the autophagic response to intracellular microbes by complement factors. Here, we review works that relate to the recently discovered connections between factors of the complement system and the functioning of autophagy in the context of host-pathogen relationship.